2019
DOI: 10.3390/ijerph16101799
|View full text |Cite
|
Sign up to set email alerts
|

Can Hypoxic Conditioning Improve Bone Metabolism? A Systematic Review

Abstract: Among other functions, hypoxia-inducible factor plays a critical role in bone–vascular coupling and bone formation. Studies have suggested that hypoxic conditioning could be a potential nonpharmacological strategy for treating skeletal diseases. However, there is no clear consensus regarding the bone metabolism response to hypoxia. Therefore, this review aims to examine the impact of different modes of hypoxia conditioning on bone metabolism. The PubMed and Web of Science databases were searched for experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 97 publications
(195 reference statements)
1
20
0
1
Order By: Relevance
“…The IH treatment significantly upregulated BMD and BMC/TV in the cancellous bone region of the mandibular condyle. The bony microstructural changes occurring in adult patients with obstructive sleep apnea (OSA) are controversial 30 . Positive BMD responses were reported for the alveolar bone of adolescent rats 10 and the lumbar vertebrae of adult rats 31 exposed to IH.…”
Section: Discussionmentioning
confidence: 99%
“…The IH treatment significantly upregulated BMD and BMC/TV in the cancellous bone region of the mandibular condyle. The bony microstructural changes occurring in adult patients with obstructive sleep apnea (OSA) are controversial 30 . Positive BMD responses were reported for the alveolar bone of adolescent rats 10 and the lumbar vertebrae of adult rats 31 exposed to IH.…”
Section: Discussionmentioning
confidence: 99%
“…Hitherto, this review has mostly examined the molecular response of bone cells to hypoxia. However, it is also pertinent to inspect the responses from the available in vivo studies (for a more comprehensive overview, please see the work of Camacho‐Cardenosa, Camacho‐Cardenosa, Timón, et al (2019). Like the other experimental approaches considered in this review, it has been suggested that different types of in vivo hypoxic exposure may elicit different responses.…”
Section: In Vivo Hypoxiamentioning
confidence: 99%
“…That was positively correlated to increasing exposure time to hypoxia, during the differentiation into osteoblasts or adipocytes, respectively, in vitro . It has been reported that bone formation decreased in sustained hypoxia[ 33 ]. Our data indicate that this may be due, in part, to the effect on MSC differentiation.…”
Section: Discussionmentioning
confidence: 99%